Clinical and Biological Manifestation of RNF168 Deficiency in Two Polish Siblings - Pietrucha, Barbara; Heropolitańska-Pliszka, Edyta; Geffers, Robert; Enßen, Julia; Wieland, Britta; Bogdanova, Natalia Valerijevna; Dörk, Thilo (Frontiers in Immunology, 2017)
Germline mutations in the RING finger protein gene RNF168 have been identified in a combined immunodeficiency disorder called RIDDLE syndrome. Since only two patients have been described with somewhat different phenotypes, there is need to identify further patients. Here we report on two Polish siblings with RNF168 deficiency due to homozygosity for a novel frameshift mutation, c.295delG, that was identified through exome sequencing. Both patients presented with immunoglobulin deficiency, telangiectasia, cellular radiosensitivity and increased alpha-fetoprotein levels. The younger sibling had a more pronounced neurological and morphological phenotype, and she also carried an ATM gene mutation in the heterozygous state. Immunoblot analyses showed absence of RNF168 protein, whereas ATM levels and function were proficient in lymphoblastoid cells from both patients. Consistent with the absence of RNF168 protein, 53BP1 recruitment to DNA double-strand breaks after irradiation was undetectable in lymphoblasts or primary fibroblasts from either of the two patients. gamma-H2AX foci accumulated normally but they disappeared with significant delay, indicating a severe defect in double-strand break repair. A comparison with the two previously identified patients indicates immunoglobulin deficiency, cellular radiosensitivity and increased AFP levels as hallmarks of RNF168 deficiency. The variability in its clinical expression despite similar cellular phenotypes suggests that some manifestations of RNF168 deficiency may be modified by additional genetic or epidemiological factors.